Mushash 163, Jordanien - Tvetmarken, Cecilie Lelek (e-Forschungsberichte des DAI, 2023)
Mushash 163 is a Neolithic site located in the semi-arid desert steppe between Amman and Azraq in north-eastern Jordan. It was identified in 2012 during the Qasr Mushash survey, following which a surface collection and a geophysical survey was carried out at the site. To date, the Neolithic period in this area is poorly understood, with most fieldwork having taken place further east in the Azraq Basin and adjacent regions. One of the main objectives of the excavations at Mushash 163 is to enable an informed assessment of the nature and timing of the settlement, as well as the economic strategies employed by the group occupying the site.